2020
DOI: 10.1128/iai.00507-20
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Cytokine Responses in the Granulomas of Asymptomatic Cattle Naturally Infected with Mycobacterium bovis in Ethiopia

Abstract: Cells (CD3+ T cell and CD68+ macrophages), cytokines (IFN-γ+ and TNF-α+) and effector molecule (iNOS+) responses were evaluated in the lymph nodes and tissue of cattle naturally infected with Mycobacterium bovis. Detailed post mortem and immunohistochemical examinations of lesions were performed on 16 cows positive for single intradermal cervical comparative tuberculin (SICCT) test which were identified from dairy farms located around the Addis Ababa City. The severity of the gross lesion was significantly hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…The NHP model has also demonstrated a higher bacterial burden in lesions arising at earlier time points and a significant reduction in bacterial burden after the onset of adaptive immunity, consistent with the findings in this study (12). Previous studies of tuberculoid granulomas of cattle have suggested that bacterial burdens are increased in late stage IV granulomas, while others have found no correlation between bacterial numbers and granuloma stage (26,41). Those studies, however, estimated bacterial burden by enumerating AFB observed in microscopic tissue sections.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The NHP model has also demonstrated a higher bacterial burden in lesions arising at earlier time points and a significant reduction in bacterial burden after the onset of adaptive immunity, consistent with the findings in this study (12). Previous studies of tuberculoid granulomas of cattle have suggested that bacterial burdens are increased in late stage IV granulomas, while others have found no correlation between bacterial numbers and granuloma stage (26,41). Those studies, however, estimated bacterial burden by enumerating AFB observed in microscopic tissue sections.…”
Section: Discussionsupporting
confidence: 89%
“…Prior studies in cattle have described the morphological heterogeneity of tuberculoid granulomas in both experimental and natural infections (26,37,41,42). The present study examined bacterial burdens of individual pulmonary tuberculoid granulomas at 30, 90, 180 and 270 days after experimental aerosol infection and revealed heterogeneity in bacterial burdens at all time points.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The severity of the lesion was higher in the lymph nodes of the thoracic region. This observation is related to the route of infection, which is predominantly a respiratory route especially in dairy cattle kept in intensive dairy farms ( 28 ). Thus, the thoracic lymph nodes are affected predominantly as they are draining the lungs.…”
Section: Discussionmentioning
confidence: 99%